Solah a testimony of success - Ismail, Fathiyah; Harun, Nur Syikri (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2021)
How could Solah bring success to our Lives? As repeatedly mentioned in many articles, Solah and success are found to be positively related. Success and Solah may at first sound like two different concepts combined altogether. When it comes to Solah, we may not be able to see how it can be one of the main contributors for a string of successes in our day-today lives.